2013
DOI: 10.3747/co.20.1202
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Women with Metastatic Breast Cancer Treated with Nab-Paclitaxel: Experience from a Single Academic Cancer Centre

Abstract: ConclusionsOur clinical experience demonstrates that most women treated with nab-paclitaxel experienced some clinical benefit. Patients achieving clinical benefit lived significantly longer than those who did not. Nab-paclitaxel was well tolerated, with the primary toxicity being mild sensory neuropathy. Nabpaclitaxel represents another treatment option, with a favourable toxicity profile, for women with mbc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
0
15
2
Order By: Relevance
“…The activity of q3w nab-paclitaxel observed in our study was higher than that previously reported in taxane-pretreated MBC patients, 31 , 36 , 37 but a cross-comparison of results is difficult because of the different characteristics of enrolled patients. We reported an ORR of 48%, including 13% complete responses, in 52 evaluable patients; 13 out of 24 women (54%) previously given paclitaxel/bevacizumab or docetaxel/capecitabine as a first-line treatment for the metastatic disease demonstrated an objective response.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The activity of q3w nab-paclitaxel observed in our study was higher than that previously reported in taxane-pretreated MBC patients, 31 , 36 , 37 but a cross-comparison of results is difficult because of the different characteristics of enrolled patients. We reported an ORR of 48%, including 13% complete responses, in 52 evaluable patients; 13 out of 24 women (54%) previously given paclitaxel/bevacizumab or docetaxel/capecitabine as a first-line treatment for the metastatic disease demonstrated an objective response.…”
Section: Discussioncontrasting
confidence: 92%
“… 32 35 To date, little information is available regarding the approved q3w schedule in the real life clinical context, because most of the data have been provided by post hoc or retrospective analyses. 36 38 Finally, the impact of such a treatment option on patient QoL has not been specifically evaluated in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Details are provided regarding sensitive neuropathy, the most common adverse event, which occurred in 41.9% of the treated patients (all grades), while grade 3 neuropathy was observed in 11.6% of cases. Regardless of the schedule of administration, women who experienced clinical benefit lived significantly longer than those who did not achieve it (17.3 versus 7.7 months, p < 0.001) [Dent et al 2013]. A subsequent study enrolled 138 MBC patients across five cancer centres in British Columbia from 2007 to 2011.…”
Section: Clinical Development Of Nab-paclitaxel In Breast Cancer Patimentioning
confidence: 99%
“…Nab-paclitaxel (Abraxane ® , Celgene) was given at a dose of 150 mg/m 2 on days 1, 8 and 15 of each chemotherapy cycle (28-day cycles) until disease progression. This dose was derived from previous studies of metastatic breast cancer [ 15 , 16 ]. Treatment was administered until disease progression and dose-adjustment criteria were based on hematological parameters.…”
Section: Methodsmentioning
confidence: 99%